IMPLICATION OF FIVE AIDS RELATED GENES IN MOTHER-TO-CHILD TRANSMISSION AND ACQUISITION OF HUMAN IMMUNODEFICIENCY VIRUS 1 IN CAMEROON - Mekue, Linda Mouafo; Nkenfou, Céline Nguefeu; Dambaya, Beatrice; Fotso, Idriss; Nguefack, Felicitée; Fainguem, Nadine; Lobè, Elise Elong; Kuiaté, Jules Roger; Ndjolo, Alexis (African Journal of Infectious Diseases (AJID), 2018)
Background: Genetic variants in the mother and/or infant have been described with evidence to be associated withmother-to-child transmission of HIV, but somehow with contradictory results depending on ethnic or geographicpopulations. We aimed at looking at the association between the allelic frequency of some genes with verticaltransmission or acquisition of HIV in Cameroon.Methodology: A total of 262 mothers (212 HIV-infected and 50 HIV non-infected) with their babies (270 in total, 42HIV exposed-infected, 178 HIV exposed non-infected and 50 HIV non-exposed) were recruited in Yaounde-Cameroon. Their genotypes for CCR5-Delta32, CCR5 promoter59029A/G, CCR2-64I, SDF1-3’A andTRIM5α-136Qwere analyzed using polymerase chain reaction and restriction fragment length polymorphisms.Results: Allelic frequencies were 14.7%, 41.9%, 9.5% and 14.7% for CCR2-64I, CCR5-59029-A/G, TRIM5α-136Q,SDF1-3’A respectively in the mothers and 18.8%, 35.9%, 11.3% and 20.5% in the babies. No delta 32 mutation in theCCR5 gene was found. The mutant genotype was most significantly frequent in the non-transmitter than in thetransmitter (p= 0.005) for the SDF-1 3'A. SDF1-3’A [Odd ratio = 1.69; 95% confidence interval: 0.1158 to 0.7277);was associated to MTCT, P = 0.008.The homozygote mutants for the CCR5-59029-G were significantly higher in theinfected than in the exposed uninfected babies (p=0.04). The mutations in the other genes were neither implicated in theacquisition nor in the transmission.Conclusion: SDF1-3’A was associated to the reduction of MTCT. The CCR5-59029-A/G favored acquisition of HIVby babies. Our study showed that polymorphisms in chemokine ligand may be involved in MTCT.